Answer:
(x+2)(9x+6)
Explanation:
This is the whole process. Skip down to the bolded important part if you want.
Going to quickly expand it again:
![9x(x+2)+6(x+2)\\9x^2+18x+6x+12\\9x^2+24x+12](https://img.qammunity.org/2022/formulas/mathematics/high-school/ezugekjagtar0zbon6fq61aau0j20tn9g8.png)
This is in the form of:
![ax^2+bx+c](https://img.qammunity.org/2022/formulas/mathematics/college/ls8sd3d86nio6ip6c65icmceeplhmx8zo2.png)
To factor a trinomial in this form, you need to find 2 numbers that multiply together to make
, and also add together to make
.
In this case,
![ac=9*12=108\\b=24\\\\18*6=108=ac\\18+6=24=b](https://img.qammunity.org/2022/formulas/mathematics/high-school/3hc4l7v4sk30314rbfk4mksxluweozxba0.png)
those 2 numbers are 18 and 6.
Then, in the above, expanded equation, you need to split b into 2 numbers, from 24 into 18 and 6.
![9x^2+24x+12\\9x^2+18x+6x+12](https://img.qammunity.org/2022/formulas/mathematics/high-school/pm01dc3891sxq6yvx9jo2epejud9y5aypq.png)
Then, split the equation in half and factor each half individually.
![(9x^2+18x)+(6x+12)\\9x(x+2)+6(x+2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/ia02fibbdga26r6ccjs9heexr74v8qhv1x.png)
Important part ==========
Now, we're right back at where we started with your question. All we need to do now is factor out the (x+2).
![9x(x+2)+6(x+2)\\(x+2)(9x+6)](https://img.qammunity.org/2022/formulas/mathematics/high-school/c9hijceirzx9iwhfvralpm3w69ja2yk557.png)
And you're done, that's all.